Activating Killer Cell Ig-Like Receptors in Health and Disease - Ivarsson, Martin A.; Michaëlsson, Jakob; Fauriat, Cyril (Frontiers in Immunology, 2014)
Expression of non-rearranged HLA class I-binding receptors characterizes human and mouse NK cells. The postulation of the missing-self hypothesis some 30 years ago triggered the subsequent search and discovery of inhibitory MHC-receptors, both in humans and mice. These receptors have two functions: (i) to control the threshold for NK cell activation, a process termed “licensing” or “education,” and (ii) to inhibit NK cell activation during interactions with healthy HLA class I-expressing cells. The discovery of activating forms of KIRs (aKIR) challenged the concept of NK cell tolerance in steady state, as well as during immune challenge: what is the biological role of the activating KIR, in particular when NK cells express aKIRs in the absence of inhibitory receptors? Recently it was shown that aKIRs also participate in the education of NK cells. However, instead of lowering the threshold of activation like iKIRs, the expression of aKIRs has the opposite effect, i.e., rendering NK cells hyporesponsive. These findings may have consequences during NK cell response to viral infection, in cancer development, and in the initial stages of pregnancy. Here we review the current knowledge of activating KIRs, including the biological concept of aKIR-dependent NK cell education, and their impact in health and disease.